Meningkatkan kemampuan mengenal bilangan melalui permainan dadu di kelompok bermain Paud terpadu Qathrun Nada Banjarmasin - Sakerani Sakerani; Hayatun Nufus (JPPTK: Jurnal Pendidikan Pembelajaran & Penelitian Tindakan, 2021)
Children's cognitive ability in counting is still very low because other efforts need to be made to improve the child's ability, in this case the researcher tries to play dice for children playing group (KB) in stating the sequence of numbers 1-10, with the hope that the child's ability will increase. Cognitive research that becomes the focus of research is a process of thinking, namely the ability of individuals to connect, assess and consider an event or event. Cognitive processes related to the level of intelligence that characterizes a person with various interests, especially aimed at ideas and learning. Classroom action research is a research that is carried out systematically, reflective of "actions" or actions taken by teachers or actors from planning to assessing real actions in the classroom in the form of teaching and learning activities to improve the conditions of learning being carried out. The subjects of this study were 12 students of Qathrun Nada Banjarmasin Integrated Family Planning, with an age range ranging from 3 to 4 years. Research data obtained through observation, interviews and documentation and data analysis. Based on learning activities in children through dice games in cycle I and Siklu II. The following is a comparison of the results of the observation of increasing cognitive abilities in children through dice games Activity 1 counting dice 1 obtains BSH results for 8 children 40% and 4 The results of the study show that the average increase in children's numeracy readiness from cycle I increases again in cycle II, namely obtaining BSH values. 10 children 71%. This means that playing dice can improve cognitive abilities in counting. From the research that has been done, it can be concluded that; Students' numeracy skills improve from pre-cycle to cycle I then to cycle II significantly with dice media in Qathrun Nada Banjarmasin Integrated Family Planning, dice media can improve children's cognitive abilities in counting activities at KB PUD Terpadu Qathrun Nada Banjarmasin.